Analisis Vegetasi Tumbuhan di Sekitar Mata Air Pada Dataran Tinggi dan Rendah Sebagai Upaya Konservasi Mata Air di Kabupaten Wonogiri, Provinsi Jawa Tengah - Yuliantoro, Dody; Frianto, Dodi (Dinamika Lingkungan Indonesia, 2019)
Wonogiri Regency is one of the regencies in Central Java that suffer drought every year. This drought was triggered by the number of springs that began to "disappear" and "die". For this reason, it is necessary to conserve springs as a way to keep the springs maintained all the time. Springs conservation activities can be carried out in two ways, namely civil engineering and vegetation. Springs conservation is needed to maintain and manage the existence of springs. Springs conservation activities can begin with the analysis of plant vegetation around springs at various heights, which are related to the density, frequency and importance of species. The existence of growing around the spring can be used as a protector and regulator of the water system. This study aims to determine the types of plants around springs in the highlands and lowlands. Activities carried out by recording all types of plants around the spring in the core zone in Wonogiri district, Central Java Province. The research method used is a line-striped method, with a 20m x 20m plot used to collect data on tree level, 10m x 10m plot size to collect data on pole level, 5m x 5m plot types for seedling / sapling data collection. Data analysis using the method of vegetation analysis is calculating the relative frequency, relative density, relative dominance and Important Value Index (IVI). The results showed that the species of trees around the spring located in the highlands and lowlands with an important value of more than 10% consisted of 15 species. The results of the Important Value Index analysis show that the species that has the highest IVI for the tree level is Beringin (Ficus benjamina), for the pole level is Bulu (Ficus annulata), and to the seedlings are Jambu Air (Syzygium aqueum).